Corporate and SME Workouts : A Manual of Best Practice - International Finance Corporation (Washington, DC, 2015)
Bank loans can become non-performing because of problems with the borrower s financial health, problems with the design or implementation of lender protection features, or both. In ascertaining how to deal with a problem loan, it is important to distinguish between a borrower s ability to pay and willingness to pay, Making this distinction is not always easy and requires effort. This manual was written as a guide for lending institution staff dealing with non-performing loans (NPLs) extended to corporations and small and medium enterprises (SMEs). It deals with both ad hoc and systemic financial distress and delves into how borrower problems may have arisen in the first place. It provides guidance to lending institutions staff responsible for handling individual problem loans and to senior managers responsible for organizing portfolio-wide asset resolution.